Editor e mercado editorial brasileiro: a edição independente crítica da Boitempo - SILVA, Paulo Cesar Garré (2021)
The present thesis has as its central interest to analyze the critical independent editorial policy of publishing house Boitempo, which also refers the analysis to the Brazilian publishing market. In its development, the Brazilian publishing market was analyzed, highlighting the importance of the editor's professional activity as a mediator in the book production chain, which begins with the writer/editor and ends with the reader/consumer. In order to understand the Brazilian publishing market, its structure and formation since its emergence in 1808 was analyzed. Currently, the Brazilian publishing market is undergoing a process of transformation with the formation of large groups of publishing companies, on the one hand, and publishing independent criticism on the other. Boitempo's editorial policy, located within the editorial field of critical independent editing, was consolidated as a form of resistance to the mass knowledge process, which demonstrates the importance of editorial engagement for the development of bibliodiversity and critical thinking in our society.